Kisar and the Archaeology of Small Islands in the Wallacean Archipelago. (3rd April 2019) - O'Connor, Sue; Mahirta,; Kealy, Shimona; Boulanger, Clara; Maloney, Tim; Hawkins, Stuart; Langley, Michelle C.; Kaharudin, Hendri A. F.; Suniarti, Yuni; Husni, Muhammad; Ririmasse, Marlon; Tanudirjo, Daud A.; et al.
ABSTRACT: The occupation of small islands presents particular challenges for people largely related to limited terrestrial resources and susceptibility to natural disasters. Nevertheless, the challenges and risks inherent in maintaining stable populations on small islands can be offset or overcome through the use of maritime technologies and exchange networks. The archaeology of Here Sorot Entapa rockshelter (HSE) on Kisar Island in the Wallacean Archipelago provides an unparalleled record for examining these issues in Southeast Asia. Kisar is the smallest of the Wallacean islands known to have a Pleistocene occupation record, and one of the smallest permanently inhabited today. Our results indicate that Here Sorot Entapa was first occupied in the terminal Pleistocene by people with advanced maritime technology who made extensive use of local marine resources and engaged in social connections with other islands through an obsidian exchange network. As a result, populations appear to have been maintained on the island for approximately 6, 000 years. In the early Holocene occupation at HSE ceased for unknown reasons, and the site was not reoccupied until the mid-Holocene, during which time a major change in the lithic resources can be observed and the exchange network appears to have ceased.